2002
DOI: 10.1302/0301-620x.84b1.0840038
|View full text |Cite
|
Sign up to set email alerts
|

The natural history and treatment of rupture of the anterior cruciate ligament in children and adolescents

Abstract: A total of 60 children and adolescents with rupture of the anterior cruciate ligament (ACL) was seen between 1980 and 1990. Observation of the 23 patients who were treated conservatively revealed that the natural history of the injury resulted in severe instability and poor function of the knee. Associated meniscal tears were present in 15 knees. Three osteochondral fractures occurred and osteoarthritic changes developed in ten knees. In 1990 therefore we introduced reconstruction of the ACL with a four-strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
1
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 16 publications
2
131
1
13
Order By: Relevance
“…Only 7 patients returned to sports, and all 16 patients experienced giving way, effusions and pain. Aichroth et al [2] reported on 23 patients who were treated conservatively and had results of severe instability and poor functional outcome. This has been our experience, too: Half (four) of the patients treated conservatively reduced their sports activity, and when examined on follow-up, seven patients showed a positive Lachman without a firm endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Only 7 patients returned to sports, and all 16 patients experienced giving way, effusions and pain. Aichroth et al [2] reported on 23 patients who were treated conservatively and had results of severe instability and poor functional outcome. This has been our experience, too: Half (four) of the patients treated conservatively reduced their sports activity, and when examined on follow-up, seven patients showed a positive Lachman without a firm endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…We classified non-operated subjects as copers at the follow-up examination if they (1) had resumed their pre-injury activity level, and (2) performed single legged hop test indexes ≥90% of the uninjured limb. Subjects who failed any of these two criteria were classified as non-copers at follow-up.…”
Section: Materials a D Methodsmentioning
confidence: 99%
“…Many children find it difficult to modify recreational activities sufficiently to avoid instability episodes. Aichroth et al [8] attempted to manage 33 children and adolescents with a mean age of 12.5 years with rehabilitation, bracing and activity modification. Ten of the children required stabilization due to increasing instability.…”
Section: Natural History Of the Acl Deficient Kneementioning
confidence: 99%
“…A number of series' report transphyseal ACL reconstructions using a variety of grafts and fixation devices with good outcomes in pediatric patients and little risk of growth disturbance [8,10,[50][51][52][53][54][55], [56•], [57], [58•]. Aronowitz et al [50] used Achilles tendon allograft with 9-10 mm tunnels in patients with a skeletal age of at least 14.…”
Section: Transphyseal Techniquesmentioning
confidence: 99%